Urinary Tract Infections: Epidemiology, Mechanisms of Infection, and Treatment - Muhammad Shahzad, Ehtesham Malik Khan, Omar Quddus Khan, Umer Bin Tariq, Arooj Sabahat (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose: The main purpose of this study was to determine the mechanism of infection and the response of preferred antibiotic treatment during this study. Study: This study was conducted from February to March 2022. The approval for this randomized study was taken by the Ethical Committee of the concerned hospital. Written informed consent was signed by all participants. Total of 110 participants who reported problems with UTIs were part of this study. Levofloxacin 750 mg per day for five days and ciprofloxacin 500 mg twice per day for ten days were given to patients for treatment. Results: The total number of patients was 110, 65 (59.09%) males and 45 (40.90%) females having a mean age of 28 ± 5, urinary tract abnormalities were observed in 28 (25.45%) patients including obstruction in 16 (14.54%) patients, stone in 8 (7.27%)cases, the neurogenic bladder was in 4 (3.63%) patients and poly-microbial etiology was in 25 (22.72%) and catheterized patients was 35 (31.81%) in which chronic catheter cases were 15 (13.63%), intermittent catheter cases were 20 (18.18%), and Complicated UTIs was found in 22 (20.02%). 55 patients were treated with levofloxacin 51 (46.36%) reported a positive response and 51 (46.36%) were not cured with a p-value of 0.05. 55 patients were treated with ciprofloxacin of which 48 (43.63%) patients were cured and 7 (6.36%) were not cured with a p-value of 0.05. The number of patients treated with levofloxacin had a higher cured percentage 46.36% than those treated with Ciprofloxacin. Conclusion: Eventually, this study demonstrated that UTIs of all the microorganisms detected during the study can be cured with levofloxacin and ciprofloxacin. While ciprofloxacin was slightly less effective in a few cases than levofloxacin. Keywords: Urinary tract infection (UTIs), Ciprofloxacin, levofloxacin, infection treatment